Identifying Islamic characters in Nussa Rarra film - Shella Ambarwati; Fachri Helmanto (Mitra Palupi, 2022)
Background: The animated cartoon film Nussa and Rarra is an animated film that displays daily stories in the world of children, Rarra is a little girl who is very cheerful and likes to play while Nussa is an older sister who loves her sister, Rarra. Purpose: The purpose of this study is to determine the formation of Islamic characters contained in the Nussa and Rarra Animations for students. Design and methods: This research was conducted using a qualitative approach to content analysis methods with descriptive analysis techniques. The data source used is the document in the form of Nussa and Rarra YouTube videos through the Nussa Official YouTube account. Results: The results of the study revealed that in the Nussa Official youtube films there were Islamic character values ​​such as honest behavior, speaking well and politely, worshiping according to the religion adopted, sincere and not being arrogant and arrogant towards others. Meanwhile, Islamic character values ​​that have not yet emerged are such as giving alms, helping others regardless of religion, spreading kindness and guarding words and deeds.